Noninvasive recording of his-purkinje system (hps) activity in man on beat-to-beat basis. - KÈ©pski R; PluciÅski Z; Walczak F (Pacing & Clinical Electrophysiology, 1982)
Since 1969 His bundle electrography has been used for diagnosis and for the study of cardiac electrophysiology. This method has employed the catheterization technique and has allowed the continuous recording of electrical activity of the specialized cardiac conduction system in every heat. Such investigation, because of its invasive nature, cannot be considered a routine test; it requires expensive instrumentation, it has physiological and technical limitations that include discomfort, a slight morbidity risk and a rather limited recorded area within the heart. In 1973 a method was developed for a noninvasive recording of the electrical activity within the P-R segment of the electrocardiogram measured from the body surface. This method which employs the signal averaging technique delivers even less medical information than intracardiac measurement. The shortcomings of this averaging method include inability to detect beat-to-beat changes in the true signal. Such a method is not useful in transient arrhythmia detection and a 'short acting' drug influence examination. The technical approach to the heat-to-beat noninvasive recording of the HPS activation signal as measured from the body surface has been proposed. Using a specially positioned electrode system, a low noise multiple parallel input amplifier and a computer for sampling, processing and plotting of the measured signal, we have obtained an output curve corresponding to the continuous beat-to-beat HPS activity.